2007
DOI: 10.1007/s10681-007-9582-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene action controlling grain yield and secondary traits in southern African maize hybrids under drought and non-drought environments

Abstract: Breeding maize hybrids for drought tolerance would significantly reduce yield loss due to drought in southern Africa. Mode of gene action controlling yield and secondary traits was investigated by mating 27 inbred lines, in sets according to a North Carolina design II scheme. The resultant 72 experimental and eight commercial hybrids were evaluated in 8 · 10 a-lattice design with two replications, in four drought and two non-drought environments. Under drought conditions, only general combining ability (GCA) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
59
9
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 14 publications
25
59
9
2
Order By: Relevance
“…Significant variation for GY under drought observed in this study was an indicator of expression of differential levels of tolerance to drought in tropical maize hybrids. Beyene et al (2013) and Derera et al (2008) also reported differential responses of tropical maize hybrids to drought stress. Evaluations of maize varieties in multiple environments reveal a range of adaptation and specific fitness for diverse environments (Setimela et al, 2007;Beyene et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Significant variation for GY under drought observed in this study was an indicator of expression of differential levels of tolerance to drought in tropical maize hybrids. Beyene et al (2013) and Derera et al (2008) also reported differential responses of tropical maize hybrids to drought stress. Evaluations of maize varieties in multiple environments reveal a range of adaptation and specific fitness for diverse environments (Setimela et al, 2007;Beyene et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies reported the presence of genetic variability for different traits in maize under saline stressed environments (Betran et al, 2003;Derera et al, 2008). Significant differences among mean squares of GCA and SCA for different maize seedling traits showed that additive and non-additive gene effects are important for these parameters.…”
Section: Discussionmentioning
confidence: 95%
“…Hal tersebut mengindikasikan genotipe 1044_30 yang bila digunakan sebagai tetua betina memberikan pengaruh lebih besar dalam pewarisan toleransi cekaman kekeringan dibanding sebagai tetua jantan. Derera et al (2007) dan Isnaini et al (2008) menyarankan penggunaan tetua betina toleran cekaman kekeringan dalam membentuk jagung hibrida toleran cekaman kekeringan.…”
Section: Pengaruh Persilangan Resiprokalunclassified